Records on anthophilous insects as pollinators of Elaeis guineensis Jacq. (Arecales: Arecaceae) in Malaysia - Siti Zulaikha Afifi,; Nurul Atiqah Mohd Yasin,; Nur Solehah Othman,; Hui Ting Tan,; Nurul Izzah Azuan,; Muhamad Azrul Shaiful Lizam,; Faiq Zulfaqar Zairy,; Asraf Mohamad Idrus,; Nur Fariza M.Shaipulah,; Norasmah Basari,; Shahrul Anuar Mohd Sah,; Mohamed Nor Zalipah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The potential role of anthophilous insects as pollinators is determined by their interactions with inflorescences. Thus, observation on the anthophilous insects was conducted at Ladang Jerangau, Terengganu, Malaysia to identify the potential pollinators of oil palm, Elaeis guineensis Jacq. Anthophilous insects from male oil palm inflorescences were recorded continuously throughout its anthesis period using digital video cameras, taken in 2019 for a total of 18 days. Data were recorded from four inflorescences, and the legitimacy of each visitation by the insects was determined based on the point of contact at the inflorescences. A total of 16 species of insects were recorded from the video observations. Amongst these species, Elaeidobius kamerunicus was the most important pollinator (VII = 1.6 x 105) given their frequent legitimate visits (656.19±464.37), and they collected abundant pollen (7205.45+2723.38) on their bodies. Moreover, males (VII = 2.5 x 105) of this species were found to be more important pollinators than the females (VII = 6.5 x 104) on the basis of their total pollen loads. Five other insects (Pyroderces sp., Dermaptera sp., Anoplolepis gracilipes, Eocanthecona sp. and Thrips hawaiiensis) were also found to exhibit regular legitimate visits (>30 visits) and are also likely pollinators. Video recordings thus provide a better understanding of insect-flower interactions in oil palm plantations. This knowledge is useful for supporting biodiversity-friendly management of the insects, which will benefit the oil palm industry in Malaysia.